Perbedaan Asupan Zat Gizi Makro antara Remaja Obesitas dan Non Obesitas di Kota Surabaya Wilayah Utara - Khoirunnisa Azzahra; Satwika Arya Pratama (Yayasan Literasi Sains Indonesia, 2025)
Adolescents are an age group that is vulnerable to nutritional problems such as obesity which can be caused by excessive macronutrient intake. This study aims to determine the differences in macronutrient intake between obese and non-obese adolescents in the North Surabaya City Region. The method used is case control. The sample consisted of 59 obese adolescents and 59 non-obese adolescents with sample selection using purposive sampling technique with gender matching method. Measurement of macronutrient intake using the Semi Quantitative Food Frequency Questionnaire instrument within a period of 3 months using interview technique. Tests on simple carbohydrate, complex carbohydrate, animal protein, and vegetable protein variables used the independent t-test because the data were normally distributed and on saturated fat and unsaturated fat variables used the Mann Whitney test because the data were not normally distributed. There were significant differences for simple carbohydrate intake (p=0,000), complex carbohydrate (p=0,044), animal protein (p=0,008), vegetable protein (p=0,014), saturated fat (p=0.000), and unsaturated fat (p=0,006).